2016
DOI: 10.1002/ange.201610776
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Electrolytic Oxygen Evolution in Neutral Media Catalyzed by a Cobalt Phosphate Nanoarray

Abstract: The topotactic conversion of cobalt phosphide nanoarray on Ti mesh into a cobalt phosphate nanoarray (Co‐Pi NA) via oxidative polarization in phosphate‐buffered water is presented. As a 3D oxygen evolution reaction (OER) catalyst electrode at neutral pH, the resulting Co‐Pi NA/Ti shows exceptionally high catalytic activity and demands an overpotential of only 450 mV to drive a geometrical catalytic current density of 10 mA cm−2. Notably, this catalyst also shows superior long‐term electrochemical stability. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 68 publications
1
42
0
Order By: Relevance
“…Since Co‐based phosphate materials were recognized as typically high efficient electrocatalyst in phosphate buffer, cobalt phosphate electrocatalyst was also prepared via the same synthesized method except that iron salt was substituted by cobalt salt (Figure S12, Supporting Information), which needs high overpotentials of 400 and 651 mV to achieve 10 and 100 mA cm −2 , respectively. Besides, the N‐Fe 2 PO 5– x ‐OT outperforms other state‐of‐the‐art electrocatalyst in neutral condition such as Co(PO 3 ) 2 , Mn 5 O 8 , Co 3 O 4 , Co‐P i NA, Co‐Fe thin films, Co 3 S 4 , Fe‐P i ‐B i , and MnO x . Consequently, it is determined that as‐prepared porous N‐Fe 2 PO 5– x also displays superior electrocatalysis activity in neutral media to literature reported systems.…”
Section: Resultsmentioning
confidence: 80%
“…Since Co‐based phosphate materials were recognized as typically high efficient electrocatalyst in phosphate buffer, cobalt phosphate electrocatalyst was also prepared via the same synthesized method except that iron salt was substituted by cobalt salt (Figure S12, Supporting Information), which needs high overpotentials of 400 and 651 mV to achieve 10 and 100 mA cm −2 , respectively. Besides, the N‐Fe 2 PO 5– x ‐OT outperforms other state‐of‐the‐art electrocatalyst in neutral condition such as Co(PO 3 ) 2 , Mn 5 O 8 , Co 3 O 4 , Co‐P i NA, Co‐Fe thin films, Co 3 S 4 , Fe‐P i ‐B i , and MnO x . Consequently, it is determined that as‐prepared porous N‐Fe 2 PO 5– x also displays superior electrocatalysis activity in neutral media to literature reported systems.…”
Section: Resultsmentioning
confidence: 80%
“…In the composite NGCO, Co‐Pi served as the main active center for OER while the NG hydrogel not only acted as conductive support but also may provide a thermodynamic advantage toward the OER. Afterward, Sun and co‐workers synthesized Co‐Pi nanoarray via electrochemical conversion of cobalt phosphide on Ti mesh (CoP NA/Ti) . The Co‐Pi NA/Ti could drive a current density of 10 mA cm −2 with an overpotential of 450 mV in 0.1 m phosphate buffer saline.…”
Section: Oer Electrocatalysts In Neutral and Acidic Electrolytesmentioning
confidence: 99%
“…In 2008, Kanan et al reported that cobalt phosphate (Co-Pi) film easily prepared by electrodeposition of Co 2+ salts in neutral water containing phosphate as a new area of exploration for non-noble catalysts that oxidize water (14). After this research, many studies have been focus on Co-Pi catalysts (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%